Austerity - Harris Dellas; Dirk Niepelt (Center for Economic Studies and ifo Institute (CESifo), 2014)
We shed light on the function, properties and optimal size of austerity using the standard sovereign debt model augmented to include incomplete information about credit risk. Austerity is defined as the shortfall of consumption from the level desired by a country and supported by its repayment capacity. We find that austerity serves as a tool for securing a more favourable loan package; that it is associated with over-investment even when investment does not create collateral; and that low risk borrowers may favour more to less severe austerity. These findings imply that the amount of fresh funds obtained by a sovereign is not a reliable measure of austerity suffered; and that austerity may actually be associated with higher growth. Our analysis accommodates costly signaling for gaining credibility and also assigns a novel role to spending multipliers in the determination of optimal austerity.
Keywords: F34; H63; 330; austerity; credit rationing; default; incomplete information; investment; growth; pooling equilibrium; separating equilibrium